ANALISIS KEBUTUHAN ASURANSI UNTUK PESERTA OLAHRAGA DIVING - Robidi; Maolani, Rukaesih A.; Marsanto, Budi (P3M Trisakti School of Insurance (TSI), 2021)
Along with the development of marine tourism in Indonesia, diving is a type of sport that is increasingly in demands. Many diving associations have sprung up, making diving a new trend in society. Diving is an outdoor activity in the open sea that has risks to health and safety compared to other outdoor activities. Diving or scuba diving is a fairly safe activity, but there are many health and safety risks that can occur that must be considered. Based on several events experienced by divers that resulted in the loss of their lives, the problem in this study is formulated as follows: 1). Does scuba diving need insurance to mitigate the risk of accidents that may be experienced while doing their activities, 2). What type of insurance is required. The results showed that scuba diving activities need insurance and the types of insurance required are: loss insurance and accident / life insurance. The research was conducted with a quantitative descriptive method. The results showed that the respondents are willing to participate in insurance